Modernization as spectacle in Africa - Bloom, Peter J.; Miescher, Stephan; Manuh, Takyiwaa (Indiana University Press, 2014)
For postcolonial Africa, modernization was seen as a necessary outcome of the struggle for independence and as crucial to the success of its newly established states. Since then, the rhetoric of modernization has pervaded policy, culture, and development, lending a kind of political theatricality to nationalist framings of modernization and Africans' perceptions of their place in the global economy. These 15 essays address governance, production, and social life; the role of media; and the discourse surrounding large-scale development projects, revealing modernization's deep effects on the expressive culture of Africa.